Development of Bioactive Patch for Maintenance of Implanted Cells at the Myocardial Infarcted Site. (31st March 2015) - Castells-Sala, C.; Vallés-Lluch, A.; Soler-Botija, C.; Arnal-Pastor, M.; Martínez-Ramos, C.; Fernandez-Muiños, T.; Marí-Buyé, N.; Llucià-Valldeperas, A.; Sanchez, B.; Chachques, J. C.; Bayes-Genis, A.; Monleón Pradas, M.; et al.
Abstract : Ischemia produced as a result of myocardial infarction might cause moderate or severe tissue death. Studies under development propose grafting stem cells into the affected area and we hypothesize that this mechanism could be enhanced by the application of a "bioactive implant." The implant herein proposed consists of a thin porous elastomeric membrane, filled with self-assembling nanofibers and human subcutaneous adipose tissue derived progenitor cells. We describe the development and characterization of two elastomeric membranes: poly(ethyl acrylate) (PEA) and poly(caprolactone 2-(methacryloyloxy)ethyl ester) (PCLMA). Both are a good material support to deliver cells within a soft self-assembling peptide and are elastic enough to withstand the stresses arising from the heartbeat. Both developed composites (PEA and PCLMA, combined with self-assembling peptide) equally facilitate the propagation of electrical pulses and maintain their genetic profile of the seeded cells. Preliminary studies with small animal models suggest that, at short times, the bioimplant shows good adhesion with the myocardium. After three days cells loaded in the patch remain alive at the implanted site. We propose that the bioactive patch (elastomeric membranes with self-assembling peptide and cells) could increase the efficacy of future cardiac cell therapy by improving cell immobilization and survival at the affected site.